PENDEKATAN MULTIKULTURAL TERHADAP PENDIDIKAN CINTA TANAH AIR PADA PEMBELAJARAN SISWA SD KELAS IV DI KECAMATAN PURWANEGARA - Bayu Iqbal Setiaji, Djariyo (MALIH PEDDAS, 2014)
This research is motivated importance of students to apply the characters in everyday life and feel comfortable while learning . Lack of students applying a positive character in daily life it will hinder the formation of personality in life , especially in learning activities . The problems revealed in this study is How the Multicultural Approach to Educatio Love Country In Fourth Grade Elementary Students Learning ? The purpose of this research is the study aimed to find out the multicultural approach to education patriotism in fourth grade elementary student learning . This research is a descriptive qualitative research that describe the events or phenomena with the data in the form of information or words . Location of the study in the Elementary School 2 Merden , SD Negeri 1 Mertasari , SD Negeri 1 Purwanegara Banjarnegara class IV Semester II . Data sourced words research results . Keywords Multicultural Approach , Love country. Engineering analysis of the data processed by means of data collection , data reduction , data display , and conclusion . Based on the analysis of research data after getting treatment Multicultural student learning using the approach to apply more characters in learning . Judging from the observation of the behavior of students in learning . Very good percentage of acceptable outcomes instruments and attract students whether or not the strategy Multicultural Approach to instill character values ââobtained results homeland Love percentage 85 % , 82 % and 87 % . From these results categorized as " good " . Therefore , it can be concluded that the " Multicultural Approach to Education Love Country In SD Class IV Student Learning acceptable and attract students " .